Performing Brazil : Essays on Culture, Identity, and the Performing Arts - Bishop-Sanchez, Kathryn; Albuquerque, Severino João Medeiros (Book collections on Project MUSE., 2015)
A field-shaping anthology by top cultural critics and practitioners representing a wide range of disciplines and art forms, Performing Brazil is the first book to bring together studies of the many and varied manifestations of Brazilian performance in and beyond their country of origin. Arguing that diverse forms of performance are best understood when presented in tandem, it offers new takes on better-known forms, such as carnival and capoeira, as well as those studied less often, including gender acts, curatorial practice, political protest, and the performance of Brazil in the United States.